Purification of swine haptoglobin by affinity chromatography. - Eurell, T E (1990)
A globin-agarose affinity chromatography technique was used to purify swine haptoglobin. This technique provides a highly specific, single-step purification method without the contamination of extraneous serum proteins reported by previous studies. Complex formation between the haptoglobin isolate and swine hemoglobin confirmed that biological activity was maintained during the purification process. Immunoelectrophoretic and Ouchterlony immunodiffusion methods revealed that the swine haptoglobin isolate cross-reacted with polyvalent antisera against human haptoglobin.